2016
DOI: 10.1161/jaha.116.003911
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil Treatment Delays the Onset of Cardiomyopathy in Dystrophin‐Deficient Hearts

Abstract: Background--Cardiomyopathy is a leading cause of mortality among Duchenne muscular dystrophy patients and lacks effective therapies. Phosphodiesterase type 5 is implicated in dystrophic pathology, and the phosphodiesterase type 5 inhibitor tadalafil has recently been studied in a clinical trial for Duchenne muscular dystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…Unfortunately, cardiac function was not evaluated in this study, as the terminal time points selected for skeletal muscle phenotype were earlier than the typical age of cardiomyopathy onset in both mdx and GRMD models (discussed in ref. 33). Future studies focused on cardiac function are needed to determine if treatment with CAT-1041 or edasalonexent prevents or slows the onset of functional cardiomyopathy in our models of DMD.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, cardiac function was not evaluated in this study, as the terminal time points selected for skeletal muscle phenotype were earlier than the typical age of cardiomyopathy onset in both mdx and GRMD models (discussed in ref. 33). Future studies focused on cardiac function are needed to determine if treatment with CAT-1041 or edasalonexent prevents or slows the onset of functional cardiomyopathy in our models of DMD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should be noted that the subjects in this study were older, ages 7 to 14, and there is precedence for investigating potential benefits of PDE inhibitors in younger DMD boys in future clinical studies. New evidence just published showed that GRMD dogs treated with tadalafil prior to detectable cardiomyopathy exhibited improved cardiac and skeletal muscle histopathological features, decreased TRPC6 levels, and delayed cardiomyopathy 209 .…”
Section: Phoshodiesterase Inhibitionmentioning
confidence: 99%
“…Application of tadalafil in dogs with golden retriever muscular dystrophy delays the onset of dystrophic cardiomyopathy. A study has shown that tadalafil decreased TRPC6 expression levels as well as permeation of Ca 2+ by increasing the overall tyrosine phosphorylation of the channel in heart [103]. T69 phosphorylation of TRPC6 was also reported in vascular smooth muscle cells.…”
Section: Phosphorylation-induced Inhibition Of Trpc6mentioning
confidence: 94%